Oxyresveratrol protects human lens epithelial cells against hydrogen peroxide-induced oxidative stress and apoptosis by activation of Akt/HO-1 pathway - Xin Hu; Yuanyuan Liang; Bo Zhao; Yongyi Wang (Elsevier, 2019)
Oxidative stress induced by hydrogen peroxide (H2O2) triggers human lens epithelial cell (HLEC) apoptosis and initiates cataract formation. Oxyresveratrol (Oxy) was reported to possess antioxidant and free radical scavenging activities. Herein, we investigated the effects of Oxy on H2O2-induced oxidative stress and apoptosis in HLECs and the associated mechanisms. Cell viability was detected by MTT assay. The oxidative damage was assessed by measuring the activities of superoxide dismutases-1 (SOD-1), catalase (CAT), glutathione reductase (GSH), and malondialdehyde (MDA). Apoptosis was analyzed by flow cytometry analysis. The changed expressions of heme oxygenase-1 (HO-1) and protein kinase B (Akt) pathways were evaluated by qRT-PCR and western blot. We found that exposure to H2O2 dose-dependently reduced cell viability, and induced oxidative stress and apoptosis in HLECs, which were reversed by pretreatment with Oxy. Oxy increased p-Akt and HO-1 expressions in H2O2-stimulated HLECs. Akt and HO-1 expressions form a regulatory axis and Oxy activated the Akt/HO-1 pathway in H2O2-stimulated HLECs. Inhibition of the Akt/HO-1 pathway by LY294002 or ZnPP attenuated the effects of Oxy on oxidative stress and apoptosis in H2O2-stimulated HLECs. In conclusion, Oxy protected H2O2-induced oxidative stress and apoptosis through activating the Akt/HO-1 pathway, suggesting the protective effect of Oxy against H2O2-induced cataract. Keywords: Oxyresveratrol, Hydrogen peroxide, Oxidative stress, The Akt/HO-1 pathway, Cataract